Unravelling Diaporthe species associated with Camellia. Issue 1 (2nd January 2016) - Gao, Yahui; Liu, Fang; Cai, Lei
Abstract : The genus Diaporthe (syn. Phomopsis ) comprises important pathogens, endophytes or saprobes with diverse host associations and worldwide distribution. Phomopsis theae is the first and hitherto the only recorded Diaporthe species on Camellia in China. The aim of this study was to investigate the Diaporthe species associated with symptomatic and asymptomatic tissues of Camellia spp. from several provinces in China. Eighty-three strains were isolated in the present study. Based on the multi-locus (ITS, HIS, TEF1, TUB) phylogenetic analyses and phenotypic characters, four novel species ( D. apiculata Y.H. Gao & L. Cai, D. compacta Y.H. Gao & L. Cai, D. oraccinii Y.H. Gao & L. Cai, D. penetriteum Y.H. Gao & L. Cai), and three known species ( D. discoidispora, D. hongkongensis, D. ueckerae ) were identified. Five strains were assigned to D. amygdali species complex and 17 strains to D. eres species complex respectively, but they could not be further identified to species level using current multi-locus phylogenetic analysis and morphological characters. Of the identified species, D. compacta and D. discoidispora are only known as endophytes. Diaporthe hongkongensis is the dominant species on Camellia, accounting for 53.3% of the frequency of occurrence. Diaporthe lithocarpus is synonymized with D. hongkongensis ; D. miriciae is synonymized with D. ueckerae . Our study revealed a high diversity of undescribed Diaporthe species on Camellia .